Pengaruh Penggunaan Media Bermain Paper Quilling Terhadap Kreativitas Anak Di RA Perwanida 2 Palembang - Jenni Sapitri; Kris Setyaningsih; Elsa Cindrya (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is entitled The Effect of Using Paper Quilling Playing Media on Children creativity at RA Perwanida 2 Palembang. The problem of this researcher is the effect of using Paper Quilling plaing media on childen’s creatyvyty at RA Perwanida 2 Palembang. This research is motivated bt the lack of children’s creativity abilites which are marked bt the lack of a less than optimal learning process in carrying out actevities. The purpose of this study is to determine the effect of using papwe quilling media at RA Perwanida 2 Palembang. The type of this study is Pre-experimental with a 0ne0 Group Pretest-Posstest design ( one group of subject). With a sample size of 18 children with 7 famele and 11 male children. The data collection technique used in this study was using the initial observation technique before used to collect data during the treatment. The test ini the froam of a score was carried out to determine the result after being given treatment and documentation in the form of photos. Data analysys techniques in the study used normality test , homogeneity test and hypotesis test. The Hypotesis result of this study obtained a count of -23.584 while the t tabbe was 1.7341 because the value of it count > t table. Then HO is rejected HA is accepted meaning there is a diference in statistical values so HA is accepsted Ho is rejected,meaning, there is aninfluence of the use of Paper Quilling Playing Medi in RA Perwanida 2 Palembang